Making your case : the art of persuading judges - Scalia, Antonin; Garner, Bryan A. (St. Paul, MN : Thomson/West, 2008)
Presents the basics of writing legal briefs and giving oral arguments, with discussions on the essentials of building a case through legal reasoning and the key elements of persuasive and successful oral pleading in the courtroom.
General principles of argumentation -- Legal reasoning -- Briefing -- Oral argument.
Includes bibliographical references (pages 213-218) and index.
Keywords: Law -- United States -- Methodology; Appellate procedure -- United States; Oral pleading -- United States; Legal composition; Forensic oratory; Persuasion (Rhetoric); Theory and methodology of law; Droit; Discours; Avocats; Juges; Expression ecrite; Expression orale; Protection juridique; Appellate procedure; Forensic oratory; Law -- Methodology; Legal composition; Oral pleading; Persuasion (Rhetoric); 2; Psychologie; Rhetoric; Lawyers; United States of America; Supreme court; Lawyers; Appeal; Pleadings; Legal reasoning; United States; United States; Educational tools (form)